Program Pelatihan Matematika Bagi Klien Corien Centre Bengkulu - Susanto, Edy; Nopriansyah; Ariyanti, Tri Dina; Luthfia , Izza (Universitas Dehasen Bengkulu, 2019)
The existence of a mathematics training program for clients of Corien Center Bengkulu Period 1 is one of the efforts to improve and increase the mathematical abilities of the parties concerned. In the training, participants were given basic mathematics learning material. The author, as a lecturer in Computer Education Study Program, Dehasen University Bengkulu, feels compelled to devote his knowledge to these students. The results of this PKM activity are: 1) Increasing the participants' knowledge and understanding of the mathematics material provided; 2) Improve participants' skills in solving problems related to mathematics in society. Knowledge in using Information Technology such as the application of computer networks to support competency exam activities